Signatures of functional bacteriome structure in a tropical direct-developing amphibian species - Martins, Renato A. (2022)
Background Host microbiomes may differ under the same environmental conditions and these differences may influence susceptibility to infection. Amphibians are ideal for comparing microbiomes in the context of disease defense because hundreds of species face infection with the skin-invading microbe Batrachochytrium dendrobatidis (Bd), and species richness of host communities, including their skin bacteria (bacteriome), may be exceptionally high. We conducted a landscape-scale Bd survey of six co-occurring amphibian species in Brazil's Atlantic Forest. To test the bacteriome as a driver of differential Bd prevalence, we compared bacteriome composition and co-occurrence network structure among the six focal host species. Results Intensive sampling yielded divergent Bd prevalence in two ecologically similar terrestrial-breeding species, a group with historically low Bd resistance. Specifically, we detected the highest Bd prevalence in Ischnocnema henselii but no Bd detections in Haddadus binotatus. Haddadus binotatus carried the highest bacteriome alpha and common core diversity, and a modular network partitioned by negative co-occurrences, characteristics associated with community stability and competitive interactions that could inhibit Bd colonization. Conclusions Our findings suggest that community structure of the bacteriome might drive Bd resistance in H. binotatus, which could guide microbiome manipulation as a conservation strategy to protect diverse radiations of direct-developing species from Bd-induced population collapses.